Mapping the Tumor Microenvironment in TNBC and Deep Exploration for M1 Macrophages-Associated Prognostic Genes - Xu, Baojin; Sun, Hefen; Song, Xiaoqing; Liu, Qiqi; Jin, Wei (Frontiers in Immunology, 2022)
Triple negative breast cancer (TNBC) remains the worst molecular subtype due to high heterogeneity and lack of effective therapeutic targets. Here we investigated the tumor and immune microenvironment heterogeneity of TNBC using scRNA-seq and bulk RNA-seq data from public databases and our cohort. Macrophage subpopulations accounted for a high proportion of tumor immune microenvironment (TIME), and M1 macrophages were associated with better clinical outcomes. Furthermore, three maker genes including IFI35, PSMB9, and SAMD9L showed a close connection with M1 macrophages. Specifically, IFI35 was positively associated with macrophage activation, chemotaxis, and migration. Also, patients with high IFI35 expression had a better prognosis. In vitro studies subsequently demonstrated that IFI35 was upregulated during the M1 subtype differentiation of macrophages. In summary, our data suggested that IFI35 maybe a promising novel target that helps to reshape macrophage polarization towards the M1 subtype for anti-tumor effects.